Studi Layanan Bank Mayapada dalam Menangani Kredit Macet Saat Pandemi Covid-19 - Gunadi Tanjaya, Erick (Jurnal Etnik: Ekonomi-Teknik, 2022)
This bad credit or loan is none other than because many companies operating in the real sector closed or went bankrupt during the pandemic, so of course it resulted in arrears or company collateral to banks as monetary companies being disrupted or failing to pay. The bankruptcy of the company that operates in the real sector also has an impact on the loss of job opportunities as employees who work for the company so that it also causes the individual credit of the employee to also fail to pay, causing an increase in the number of bad loans or Non-Performing Loans at the bank. The purpose of this study is to explain how Bank Mayapada Services in Handling Bad Credit During the Covid-19 Pandemic. The research method used by the researcher is qualitative. With a sample of 5 respondents in Surabaya who experienced bad loans, the conclusion is that Bank Mayapada's Services in Handling Bad Loans in Surabaya already have satisfactory results for Bank Mayapada customers